1997
DOI: 10.1542/peds.100.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Infasurf (Calf Lung Surfactant Extract) to Survanta (Beractant) in the Treatment and Prevention of Respiratory Distress Syndrome

Abstract: Infants treated with Infasurf have a modest benefit in the acute phase of RDS. Infasurf seems to produce a longer duration of effect than Survanta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 24 publications
2
128
0
1
Order By: Relevance
“…Owing to the small sample size, differences detected in the secondary outcome measures are subject to type II error and need to be considered with caution. However, our results are similar to those of Bloom et al 5 The method we chose to measure dynamic compliance is readily available to the clinician caring for infants with RDS, can be used to guide ventilator management, and is a good trending device. The method may not be sensitive enough in infants with uncuffed endotracheal tubes who move spontaneously 11 and may partially explain the inability to demonstrate differences in immediate change in lung mechanics following surfactant administration.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Owing to the small sample size, differences detected in the secondary outcome measures are subject to type II error and need to be considered with caution. However, our results are similar to those of Bloom et al 5 The method we chose to measure dynamic compliance is readily available to the clinician caring for infants with RDS, can be used to guide ventilator management, and is a good trending device. The method may not be sensitive enough in infants with uncuffed endotracheal tubes who move spontaneously 11 and may partially explain the inability to demonstrate differences in immediate change in lung mechanics following surfactant administration.…”
Section: Discussionsupporting
confidence: 85%
“…3 In another study comparing multiple surfactant preparations, premature lambs treated with Infasurf had improved pulmonary compliance demonstrated within 1 hour surfactant administration compared to those treated with Survanta. 4 In a controlled trial comparing the efficacy of Infasurf and Survanta in premature infants, the group treated with Infasurf required significantly less oxygen and had significantly lower P aw 1 hour after surfactant administration, 5 but measurements for pulmonary compliance were not reported. Extrapolating immediate improvement in compliance from animal studies 3,4 suggests the potential for rapid increase in tidal volume delivery and lung overdistention and injury following surfactant administration if the ventilator is used in a pressure-targeted modality and pressure is not promptly decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Survanta was predominantly used to treat the initial RDS in our patients based on increased survival compared to Infasurf for patients with birth weight <600 g. 11 Once Infasurf became available at our institution, it was primarily used to treat the postsurfactant slump in our patients due to the laboratory evidence showing better reduction in surface tension in the face of surfactant inactivation. 12,13 The severity of lung disease and response to the repeat course of surfactant was evaluated by calculating a RSS.…”
Section: Methodsmentioning
confidence: 99%
“…Anzueto et al [136] administered nebulized Exosurf® vs. placebo to 725 adults with ARDS secondary to sepsis and found no improvement in any measure of oxygenation and no effect on morbidity or mortality. However, interpretation of these negative results is confounded because both laboratory and clinical studies have documented that Exosurf® has low activity compared to animal-derived surfactants [51, [113][114][115][116][117][142][143][144][145], and aerosolization has not been shown to be as effective as airway instillation in delivering surfactant. Gregory et al [137] reported small benefits in oxygenation in a controlled trial in adults with ARDS who received four 100 mg/kg doses of Survanta®, but with no overall advantage in survival in the 43 surfactant-treated patients studied.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%